2020
DOI: 10.1108/ijm-12-2019-0541
|View full text |Cite
|
Sign up to set email alerts
|

The HPWS and AMO: a dynamic study of system- and individual-level effects

Abstract: PurposeDrawing on the dynamic model of ability, motivation, opportunity (AMO) for human resource research, this study aims to examine how organizational system-level (i.e. the high-performance work system (HPWS)) and individual-level AMO affect employees' performance. Specifically, this paper proposes that employee task performance is resultant from the integration of system- and individual-level AMO factors with employee contextual performance.Design/methodology/approachA survey design is employed with data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 55 publications
2
25
0
2
Order By: Relevance
“…Ability-motivation-opportunity (AMO) framework is the most used to explain the influence of human resource practices at the organizational level such as company performance. Such practices should be designed to enhance the ability, motivation and opportunity of the individuals (Edgar et al, 2020). Renwick et al (2008Renwick et al ( , 2013 introduce AMO as an underlying framework used to clarify GHRM practices and their role.…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
“…Ability-motivation-opportunity (AMO) framework is the most used to explain the influence of human resource practices at the organizational level such as company performance. Such practices should be designed to enhance the ability, motivation and opportunity of the individuals (Edgar et al, 2020). Renwick et al (2008Renwick et al ( , 2013 introduce AMO as an underlying framework used to clarify GHRM practices and their role.…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
“…This is a major reason that in recent times, it has been widely investigated and studied at both the employee and organizational level. Edgar et al (2020) suggested that there is a need to study the different dimensions of HR practices in HPWS that influence employee performance. There is confusion about how HPWS may influence employee performance (Han et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A social identification develops the relationship between HPWS and affective commitment. Also, it mediates the relation-ship between HPWS and job satisfaction (Young et al, 2010), and HPWS is used as a measuring tool for organizational systems (Edgar et al, 2020).…”
Section: High-performance Working System (Hpws)mentioning
confidence: 99%